2014
DOI: 10.3892/ijmm.2014.1893
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of gene expression in endothelial cells in response to high LET nickel ion irradiation

Abstract: Abstract. Ionizing radiation can elicit harmful effects on the cardiovascular system at high doses. Endothelial cells are critical targets in radiation-induced cardiovascular damage. Astronauts performing a long-term deep space mission are exposed to consistently higher fluences of ionizing radiation that may accumulate to reach high effective doses. In addition, cosmic radiation contains high linear energy transfer (LET) radiation that is known to produce high values of relative biological effectiveness (RBE)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…NF- κ B can promote apoptosis in endothelial cells when endothelium is subjected to irradiation such as ultraviolet B (UVB) and hadron; this action is based on the upregulation of tumor necrosis factor alpha (TNF- α ) and is significantly enhanced upon costimulation with interleukin-1 (IL-1) and IL-6 [27]. Apart from UVB radiation, NF- κ B is also commonly activated by oxidants such as H 2 O 2 .…”
Section: The Role Of Each Specific Pathway Associated With Oxidatimentioning
confidence: 99%
“…NF- κ B can promote apoptosis in endothelial cells when endothelium is subjected to irradiation such as ultraviolet B (UVB) and hadron; this action is based on the upregulation of tumor necrosis factor alpha (TNF- α ) and is significantly enhanced upon costimulation with interleukin-1 (IL-1) and IL-6 [27]. Apart from UVB radiation, NF- κ B is also commonly activated by oxidants such as H 2 O 2 .…”
Section: The Role Of Each Specific Pathway Associated With Oxidatimentioning
confidence: 99%
“…After 56 Fe-ion exposure, p53 and genes controlling apoptosis were upregulated [79]. In the human endothelial cell line EA.hy926, 58 Ni-ion (LET 183 keV/lm) exposure induced expression of genes involved in endothelial permeability and apoptosis signaling [80].…”
Section: Cardiovascular Systemmentioning
confidence: 99%
“…[6][7][8] Space experiments and ground-based simulations have also shown that both factors induce marked changes in gene expression. [9][10][11] Despite these documented relationships, major uncertainties remain regarding the exact contribution of IR and μg to human disorders and the underlying molecular and cellular mechanisms. For instance, it is not clear to what extent HZE-induced DNA damage or μg-induced cytoskeletal reorganizations persist upon prolonged exposure, if and how physical or biochemical communication between cells and within a multi-cellular organism contributes to the response, or how both factors jointly affect spatiotemporal gene expression patterns, differentiation and development.…”
Section: Relevance Of Biological Space Researchmentioning
confidence: 99%
“…Both adherent (e.g., carcinoma cells and fibroblasts) and suspension cells (e.g., lymphocytes), primary and transformed, have been used in space and ground-based experiments to study the complex influence of a reduced gravitational force on mammalian cell growth and function, including effects on gene expression 9,10,28 and cytoskeletal organization 29,30 as well as the effects of cosmic radiation on DNA damage repair 5,11 and cytokine secretion. 5,31 Nevertheless, most cellbased studies are being performed with individual cells, either in suspension, or as adherent monolayers cultured on hard, flat surfaces.…”
Section: Biological Model Systems For Space Sciencementioning
confidence: 99%